Reduced survival after autologous stem cell transplantation in myeloma and lymphoma patients with low vitamin D serum levels. Issue 4 (29th July 2020) - Eicher, Florian; Mansouri Taleghani, Behrouz; Schild, Christof; Bacher, Ulrike; Pabst, Thomas
Abstract: High‐dose chemotherapy (HDCT) with autologous stem cell transplantation (ASCT) is applied for consolidation in myeloma and relapsing lymphoma patients. Vitamin D (VitD) exerts effects during hematopoietic stem cell proliferation, differentiation and interactions with the immune system. VitD deficiency is frequent in patients with hematological malignancies, but its prognostic relevance after ASCT remains unclear. We investigated the effect of VitD serum levels in patients with lymphomas and myeloma at ASCT on progression‐free (PFS) and overall survival (OS). The cohort (n = 183) was divided into two groups: 81 (44%) had VitD levels >52 nmol/L and 102 (56%) ≤52 nmol/L at ASCT. VitD levels >52 nmol/L were associated with better PFS ( P = 0.0194) and OS ( P = 0.011). Similarly, when evaluating myeloma patients alone, patients with lower VitD levels (≤52 nmol/L) had inferior PFS ( P = 0.0412) and OS ( P = 0.049). Finally, the multivariate analysis was consistent that varying VitD levels were significantly associated with OS ( P = 0.0167), also when stratifying patients in groups with VitD levels > versus ≤52 nmol/L ( P = 0.0421). Our data suggest that reduced serum VitD levels in myeloma and lymphoma patients undergoing HDCT/ASCT are associated with inferior outcome. Optimizing VitD levels before ASCT may be warranted.